2021
DOI: 10.3892/mmr.2021.11839
|View full text |Cite
|
Sign up to set email alerts
|

miR‑653‑5p suppresses the growth and migration of breast cancer cells by targeting MAPK6

Abstract: Breast cancer is the worldwide leading cause of cancer-related deaths among women. Increasing evidence has demonstrated that microRNAs (miRNAs) play critical roles in the carcinogenesis and progression of breast cancer. miR-653-5p was previously reported to be involved in cell proliferation and apoptosis. However, the role of miR-653-5p in the progression of breast cancer has not been studied. In the present study, it was found that overexpression of miR-653-5p significantly inhibited the proliferation, migrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…U6 was used as an endogenous control. The 2 –ΔΔCt method was used to evaluate relative gene expression [ 21 ]. The primers used in our study were listed as follows: circ007293 (F: 5ʹ-TGCCGGAAGAGGGGTTCCATG-3ʹ; R: 5ʹ-GCGAAGATTCTGCCCATCATGT-3ʹ), miR-653-5p (F: 5ʹ-GTGTTGAAACAATCTCTACTG-3ʹ; R: 5ʹ-GAACATGTCTGCGTATCTC-3ʹ), PAX6 (F: 5ʹ- TCTTTGCTTGGGAAATCCG-3ʹ; R: 5ʹ- CTGCCCGTTCAACATCCTTAG-3ʹ), and GAPDH (F: 5ʹ-TATGATGATATCAAGAGGGTAGT-3ʹ; R: 5ʹ-TGTATCCAAACTCATTGTCATAC-3ʹ).…”
Section: Methodsmentioning
confidence: 99%
“…U6 was used as an endogenous control. The 2 –ΔΔCt method was used to evaluate relative gene expression [ 21 ]. The primers used in our study were listed as follows: circ007293 (F: 5ʹ-TGCCGGAAGAGGGGTTCCATG-3ʹ; R: 5ʹ-GCGAAGATTCTGCCCATCATGT-3ʹ), miR-653-5p (F: 5ʹ-GTGTTGAAACAATCTCTACTG-3ʹ; R: 5ʹ-GAACATGTCTGCGTATCTC-3ʹ), PAX6 (F: 5ʹ- TCTTTGCTTGGGAAATCCG-3ʹ; R: 5ʹ- CTGCCCGTTCAACATCCTTAG-3ʹ), and GAPDH (F: 5ʹ-TATGATGATATCAAGAGGGTAGT-3ʹ; R: 5ʹ-TGTATCCAAACTCATTGTCATAC-3ʹ).…”
Section: Methodsmentioning
confidence: 99%
“… 37 And yet, its tumor-suppressive role was also depicted in breast cancer, showing overexpression of miR‑653‑5p contributes to breast cancer cells in vitro proliferation and migration. 38 In lung cancer, miR-653-5p silence favors cellular growth and invasion in vitro. 26 However, its role in LUAD gefitinib resistance remained elusive.…”
Section: Discussionmentioning
confidence: 99%
“…miR-653-5p depletion can significantly block the protective role of circNRIP1 silencing in PTC cell malignancy. miR-653-5p showed downregulation played a role in inhibiting the malignant phenotype of tumors, such as breast cancer, prostate cancer, cervical cancer, gastric cancer, lung cancer, ovarian cancer, and melanoma [ 34 40 ]. Consistent with a previous study [ 41 ], our study showed that miR-653-5p can also inhibit PTC cell proliferation and invasion, which further enriches our interpretation of miR-653-5p role in tumors.…”
Section: Discussionmentioning
confidence: 99%